Түүхээ үзэх Монгол ухаан - Хүүхэнбаатар, Дашдаваа (Historia Mongolarum, 2008)
Ардын хувьсгалын жилүүдийн түүхэнд болсон хэрэг явдлыг өнөөгийн Монгол хүн өөрөө ямар нэг үзэл сурталгүй бусдаас хараат бус Монгол үндэсний үзлийн үүднээс үзэх өөрийн бодлогын заримаас гаргав. The article describes the trends with which the Mongolians perceived their history during the modern period. In particular, the wake of the 1921 National Revolution brought an immense wave of nationalist interpretation of history, yet to be suppressed and supplanted by the official Marxist, anti-national in nature, historiography. It was only following the 1990 pro-democracy movement that nationalism was reintroduced as the core perception of history.